EU common fisheries policy and fisheries partnership agreements - Challenges for ACP countries: Agritrade Executive Brief Update 2013 - Technical Centre for Agricultural and Rural Cooperation; Eastern Africa Grain Council (Technical Centre for Agricultural and Rural Cooperation, 2013)
Finalized in mid-2013, the new Common Fisheries Policy (CFP) will cover, through the financing of the European Maritime and Fisheries Fund (EMFF), expenditures related to the EU’s external fisheries policy, including: financial contributions to Fisheries Partnership Agreements (FPAs); participation in regional fisheries management organisations for tuna; and, in all probability, funding for temporary cessation of activities when fisheries agreement protocols are not renewed on time. Within the CFP, the main framework for ACP–EU fisheries relations is provided by FPAs and by EU initiatives in regional fisheries management organizations. This Executive Brief analyses in detail the 2012-13 developments prior to the entry into force of the new CFP, focusing mainly on the implications for the fisheries sector in ACP countries.